PENYAJIAN INFORMASI BERBASIS MULTIMEDIA DI KANTOR PELAYANAN TELEKOMUNIKASI YOGYAKARTA - Herawati, Nuniek (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
In the very fast development of technology and information, the need of information for supporting information service which is needed by all private or government institutions. The providing needs can be supported by a multimedia that shows or present information. At â€œPT Telekomunikasi Indonesia Tbkâ€, when the more of needs of information and the more telecommunication service user is, so an information presentation based on multimedia is necessary to be made that can be applied to work station. It is an alternative for helping customer and visitor on getting information without queueing at customer service counter.This research produce information system in an interactive user interface presentation and easy to be used by customer and visitor. System that is produced is able to work globally and intranetly, both are client-side.